Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1063/1.4930038
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the hybridization bandgap by meta-molecules with in-unit interaction

Abstract: In this paper, we demonstrate that the hybridization bandgap (HBG) can be tuned conveniently by deep subwavelength meta-molecules with in-unit interaction. Spontaneous-emission-cancellation-like (SEC-like) effect is realized in a meta-molecule by introducing the destructive interference of two detuned meta-atoms. The meta-atoms consisting of subwavelength zero-index-metamaterial-based resonators are side-coupled to a microstrip. Compared to conventional HBG configurations, the presence of in-unit interaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In spontaneous emission cancellation (SEC) analogue, the SEC-like effect is achieved in a meta-molecule by properly tailoring the destructive interference of two different emitting meta-atoms [31,32]. It is noteworthy that, in contrast to the EIT analogue, the SEC-like effect realized by meta-molecules has an extremely deep stop-band in the transmission spectrum [33][34][35]. Up to now, a large number of researches have confirmed that it is feasible to realize EM modulators in actively controlled EITlike meta-molecules [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In spontaneous emission cancellation (SEC) analogue, the SEC-like effect is achieved in a meta-molecule by properly tailoring the destructive interference of two different emitting meta-atoms [31,32]. It is noteworthy that, in contrast to the EIT analogue, the SEC-like effect realized by meta-molecules has an extremely deep stop-band in the transmission spectrum [33][34][35]. Up to now, a large number of researches have confirmed that it is feasible to realize EM modulators in actively controlled EITlike meta-molecules [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…To date, controllably coupling metamaterials in the manner required to mimic vdW heterostructures remains challenging, despite several promising layered designs [18][19][20] . Meanwhile, coupling-induced hybridization effects were investigated in systems of neighboring acoustic resonators [21][22][23] , but whether they can be used to imitate vdW heterostructures is an open question.…”
Section: Introductionmentioning
confidence: 99%